Maximal covers of finite groups. Issue 2 (1st February 2020) - Bastos, Raimundo; Lima, Igor; Rogério, José R.
Abstract: Let λ ( G ) be the maximum number of subgroups in an irredundant covering of the finite group G . We prove that if G is a group with λ ( G ) ≤ 6, then G is supersolvable. We also describe the structure of groups G with λ ( G ) = 6. Moreover, we show that if G is a group with λ ( G ) < 31, then G is solvable.